Association of serum per- and polyfluoroalkyl substances and gestational anemia during different trimesters in Zhuang ethnic pregnancy women of Guangxi, China. (December 2022) - Liao, Qian; Tang, Peng; Pan, Dongxiang; Song, Yanye; Lei, Lei; Liang, Jun; Liu, Bihu; Lin, Mengrui; Huang, Huishen; Mo, Meile; Huang, Chengtuo; Wei, Ming; et al.
Abstract: Background: Gestational anemia is a complication of pregnancy, and a low level of hemoglobin (Hb) has been linked to adverse pregnancy outcomes. Previous studies reported that PFASs were more strongly associated with Hb than red blood cells, indicating that Hb is more susceptible to the effect of PFASs. However, the evidences regarding the effects of per- and polyfluoroalkyl substances (PFASs) on gestational anemia are currently limited. Therefore, it is important to explore the effects of PFASs on anemia in Chinese pregnant women. Methods: A total of 821 pregnant women were recruited between June 2015 and April 2019 in the Guangxi Zhuang Birth Cohort. The concentrations of PFASs were assessed in maternal serum before 12 gestational weeks. To determine both individual and combined associations of PFASs exposure with anemia in the three stages of pregnancy, binary logistic regression, Bayesian kernel machine regression (BKMR), and weighted quantile sum (WQS) regression models were employed. Results: In single-pollutant analysis, maternal exposure to perfluorododecanoic acid (PFDoA) and perfluoroheptanoic acid (PFHpA) were associated with anemia in the first trimester, exposure to PFHpA and perfluorobutanesulfonic acid (PFBS) were associated with anemia in the second trimester, and exposure to perfluorodecanoic acid (PFDA) and perfluorononanoic acid (PFNA) were associated with anemia in the third trimester. Notably, perfluoroundecanoic acid (PFUnA) had a nonlinear association with anemia in the third trimester. In multiple-pollutant analysis, a positive association of PFDoA with anemia in the first trimester and a negative association of PFBS with anemia in the second trimester were confirmed by BKMR. Exposure to PFASs mixture was not associated with anemia in all three trimesters. In WQS, there was a significantly negative association between the PFAS mixture and anemia in the second trimester. Conclusion: Maternal exposure to PFASs is associated with gestational anemia in different trimesters. Graphical abstract: Image 1 Highlights: Maternal exposure to PFDoA was related to a higher risk of gestational anemia in the first trimester. Maternal exposure to PFBS was related to a lower risk of gestational anemia in the second trimester. An inverted U-shaped relationship for PFUnA and gestational anemia in the third trimester. There was no significant correlation between PFASs mixture and gestational anemia in all three trimesters.